Acute injuries in soccer, ice hockey, volleyball, basketball, judo, and karate: analysis of national registry data - Kujala, U. M.; Taimela, S.; Antti-Poika, I.; Orava, S.; Tuominen, R.; Myllynen, P. (British Medical Journal, 1995)
OBJECTIVE--To determine the acute injury profile in each of six sports and compare the injury rates between the sports. DESIGN--Analysis of national sports injury insurance registry data. SETTING--Finland during 1987-91. SUBJECTS--621,691 person years of exposure among participants in soccer, ice hockey, volleyball, basketball, judo, or karate. MAIN OUTCOME MEASURES--Acute sports injuries requiring medical treatment and reported to the insurance company on structured forms by the patients and their doctors. RESULTS--54,186 sports injuries were recorded. Injury rates were low in athletes aged under 15, while 20-24 year olds had the highest rates. Differences in injury rates between the sports were minor in this adult age group. Overall injury rates were higher in sports entailing more frequent and powerful body contact. Each sport had a specific injury profile. Fractures and dental injuries were most common in ice hockey and karate and least frequent in volleyball. Knee injuries were the most common cause of permanent disability. CONCLUSIONS--Based on the defined injury profiles in the different sports it is recommended that sports specific preventive measures should be employed to decrease the number of violent contacts between athletes, including improved game rules supported by careful refereeing. To prevent dental injuries the wearing of mouth guards should be encouraged, especially in ice hockey, karate, and basketball.